Falls in paediatric Charcot-Marie-Tooth disease: a 6-month prospective cohort study. Issue 6 (13th August 2018) - Kennedy, Rachel A; Carroll, Kate; Hepworth, Graham; Paterson, Kade L; Ryan, Monique M; McGinley, Jennifer L
Abstract : Objective: To prospectively study falls in children and adolescents with Charcot-Marie-Tooth disease (CMT). Design: Prospective cohort study. Setting: Neuromuscular outpatient clinic of a tertiary paediatric hospital. Patients: Sixty children and adolescents ('children') aged 4–18 years, 30 with CMT and 30 typically developing (TD). Main outcome measures: Falls rate over 6 months and falls characteristics questionnaire. Results: Twenty-two children with CMT reported falling at least once in 6 months compared with eight TD children (CMT 2819 (0–1915), TD 31 (0–6) total falls (range)). Detailed falls characteristics were collected from 242 individual falls (CMT 216, TD 26). Injurious falls were reported by 19 children with CMT (74 falls) compared with 2 TD children (3 falls), with cuts, grazes and bruising most common. No fractures were sustained and no child required hospitalisation. However, 12 injuries from falls in children with CMT required management by a healthcare provider, versus none in TD children. Tripping was the most common mechanism of falls in both groups. Age was the strongest predictor of falls (ρ=−0.53, p=0.006) with all children (CMT and TD) aged <7 years falling. Balance was the strongest impairment-related predictor of falls (ρ=−0.47, p=0.02). The conservative estimate of risk of falls in children and adolescents with CMT was 33 times higher than their TD peers (incidence rate ratio=32.8, 95% CI 10.2 to 106.0). Conclusions: Children and adolescents with CMT fall more often than TD peers and sustain more injuries when they fall.